Sexual violence stigma experiences among refugee adolescents and youth in Bidi Bidi refugee settlement, Uganda: Qualitative insights informed by the stigma power process framework - Logie, Carmen H.; Okumu, Moses; Coelho, Madelaine; Loutet, Miranda G.; Berry, Isha; Lukone, Simon Odong; Kisubi, Nelson; Musoke, Daniel Kibuuka; Kyambadde, Peter (SSM - mental health, 2023)
There are over 100 million forcibly displaced persons who experience elevated risks for sexual violence. Sexual violence stigma can have immediate and long-lasting effects on social and health outcomes among survivors. There is a dearth of information on the experiences of sexual violence stigma among refugee adolescents and youth, particularly in low and middle-income contexts where most forcibly displaced persons are hosted. Our study focuses on understanding the lived experiences of sexual violence stigma among refugee adolescents and youth in Bidi Bidi Refugee Settlement, Uganda. This qualitative study involved twelve individual in-depth interviews and six focus groups in Bidi Bidi with refugee youth aged 16–24, refugee elder interviews (n = 8), and service provider interviews (n = 10). We explored experiences and impacts of sexual violence stigma, including accessing supportive resources. We conducted thematic analysis informed by the Stigma Power Process framework. This framework examines how social processes of stigma serve to keep people ‘in’, ‘down’, and ‘away’. Participant narratives highlighted negative cultural conceptions of sexual violence survivors and of women and girls, as well as daily indignities targeting survivors that reinforced their lower status. Shaming sexual violence survivors as ‘immoral’ operated to keep people ‘in’ the social order where it was expected that ‘moral’ persons would not experience sexual violence. Fear of such judgment, and wanting to stay ‘in’, produced barriers for survivors to access healthcare and legal support. Participants reported community-level blame and punishment kept them ‘down’, and community isolation and rejection kept them ‘away’. At the individual level, survivors were kept ‘down’ through internalizing shame, low self-esteem, self-isolation, and hiding. Findings signal the need to address the far-ranging impacts of sexual violence stigma on refugee youth health, wellbeing, and rights. Meaningfully engaging refugee youth and communities in reducing sexual violence stigma must concomitantly transform inequitable gender norms and power relations.